(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Although foam concrete was initially intended to be avoid filler and insulating material, interest in its structural qualities has grown again due to its reduced weight, material savings, and potential for extensive use of waste materials like fly ash. This paper’s main objective is to review the present state of knowledge on foam concrete, where sand is partially replaced by glass powder, fly ash, and blast furnace slag in various weights and proportions. The review highlights the necessity for creating new pathways by doing in-depth research on materials, mixture design, and methods to maximise the potential of this material for structural applications.